Developing an effective social emotional learning program for countering school bullying: An evaluative exploratory study - Sameh, Ahmed (AUC Knowledge Fountain, 2017)
The meaning of school bullying which incorporates a number of key components: bodily, mental assault, use of harsh and rude language, or terrorizing in attempt to bring about a feeling of fright, anxiety, submission or damage to the bullied. Bullying has serious repercussions to the extent that it might lead a victim to ending their lives (Farrington & Ttofi, 2009). Kazarian and Ammar (2013) linked bullying with the spread of negative health conditions such as insomnia, anorexia, and obesity as well as social behaviors such as the use of drugs and alcohol, aggression, and the use of weapons. "Sixty percent of identified bullies have a criminal conviction" (Newman, 2007: p. 568). The aim of this evaluative exploratory research is to showcase the effect of a program delivered to school students of ages 12-14 that is designed to help in eradicating school bullying by using Social and Emotional Learning techniques (SEL). SEL develops the students' self- awareness, social awareness, self-management and organization, responsible problem solving, and relationship management. School-based SEL programs developed to prevent school violence, including bullying, are derived from the belief that academic skills are essentially linked to youth's ability to manage and regulate emotions, and to communicate and problem-solve challenges and interpersonal conflicts. Hence based on a fieldwork conducting one to one interviews with fifteen students and five teachers, the SEL program was implemented in a private school in Egypt and its effectiveness was measured by the 62 respondents through open-ended surveys. The findings of the study explain students' perceptions of bullying and the extent to which it is practiced in their school as well as its causing factors. In addition, the study reveals, the perceived effect of the program on participating students and its contribution towards creating a bullying- free school.